STRATEGI BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) DALAM PENGURANGAN RISIKO BENCANA ALAM DI KABUPATEN BIMA - Haeril Haeril; Taufik Irfadat; Mas’ud Mas’ud (Jurnal Studi Ilmu Pemerintahan, 2022)
The urgency of this research is to explain the strategy of the Disaster Management Agency in reducing disaster risk, reducing vulnerability, and increasing the capacity of the Government and Society in dealing with disasters in Bima Regency. As a leading sector in disaster management efforts, BPBD acts as a coordinator, facilitator, motivator, as well as implementing programs. The strategies implemented to reduce disaster risk in Bima Regency are strengthening institutional rules and institutions, integrated disaster management planning, implementing disaster education and research, capacity building, collaboration, and community participation, implementing disaster reduction strategies, and seeking to increase the effectiveness of disaster management. disaster emergency. From the various disaster management strategies above, the estuary is to seek integrated and collaborative disaster management as a new paradigm in more effective disaster risk reduction in Bima Regency.